Impact Marketing Techniques: Instagram, WhatsApp, and Consumer Predisposition Acquire Prepared Foods - Diantoro, Karno; Sinar, Corizon; Rinaldo; Rohman, Abdur (Indonesian Scientific Publication, 2024)
With the growth of social media and messaging platforms, businesses are investigating new marketing methods to reach and impact consumer behavior. This study investigates the effect of marketing strategies on Instagram and WhatsApp on consumers' inclination to buy prepared, home-cooked meals. It looks into how companies use these platforms' interactive and visual elements to market their products and influence customer choices. The research examines consumer surveys and marketing initiatives data to identify the primary drivers of engagement and buy intentions. It investigates how direct messaging, targeted advertising, and influencer marketing affect customer attitudes and decision-making. The study also explores the ethical issues of these marketing strategies and how they may affect consumers' privacy and autonomy. This research intends to increase awareness about responsible practices that respect consumer interests while guiding firms in optimizing their methods by offering insights into the efficacy of social media and messaging app marketing strategies. The results add to the growing conversation about how digital marketing impacts food consumption habits and how consumer-business relationships are changing.